PERLINDUNGAN HUKUM ATAS PELANGGARAN TERKAIT KONSUMEN JASA KEUANGAN DALAM TRANSAKSI MELALUI MEDIA TELEPON (Studi Peraturan Otoritas Jasa Keuangan No. 1/POJK.07/2013) - Sejahtera Giovani (2021)
The development and progress of telecommunications have encouraged progress in information technology, especially the telephone. With this progress, banks are used to provide financial services as providers of efficient payment mechanisms and instruments for customers or consumers. Based on the precautionary principle through standard agreements by Article 1338 of the Civil Code. The Financial Services Authority Regulation Number: 1/POJK.07/2013 concerning the Protection of Financial Services Consumers as the implementation of Article 31 of the OJK Law is made to protect consumers. However, the implementation has not been achieved optimally due to the bank's negligence in implementing the precautionary principle, and it can be seen in the case of breaking into customer data resulting in losses for customers. The problem is 1) What are the legal protection barriers for consumers of banking financial services transactions by telephone based on laws and regulations?2) What are the legal protections for consumers of financial service transactions by telephone based on the Financial Services Authority Regulation Number: 1/POJK.07/2013? By using a normative juridical approach research method, it was found that 1) Barriers to consumer protection occur because the banking sector does not implement the prudential principle, resulting in data breaches that result in losses for customers. 2) Efforts made by OJK in the form of providing rules for the complaint process by both consumers and members of the public and if there are violations, sanctions can be imposed, suggestions in this study are 1) there is a need for new norms in the banking law so that consumers understand more about their rights and protection. Law on their rights. 2) it is necessary to increase efforts for customers as consumers and the public, including entrepreneurs, to understand their position in financial service activities.